SUSTAINABLE CONSUMPTION OF RURAL AND URBAN HOUSEHOLDS IN POLAND - Monika Utzig (Acta Scientiarum Polonorum. Oeconomia, 2017)
Sustainable consumption is the consumption of goods and services satisfying fundamental needs, increasing life quality, reducing resource use, degradation and pollution along the whole lifecycle of product or service. The aim of the study is to examine whether the consumption of urban households is more sustainable compared to rural ones and to identify directions of changes in this regard. The analysis was realised on the basis of Household Budget Survey conducted by the Central Statistical Office of Poland (CSO) in the span of 2006–2015. The results show that urban and rural households in Poland shift their consumption patterns towards less sustainable as well as urban households’ consumption pattern in some areas is less sustainable that urban ones.